General requirements for Home and Building Electronic Systems (HBES) and Building Automation and Control Systems (BACS). Smart grid. Application specification. Interface and framework for customer. Interface between the Home / Building CEM and Resource manager(s). Data model and messaging Part 12-2, (3rd May 2022) - British Standards Institution,
No abstract available